2014
DOI: 10.1104/pp.114.236083
|View full text |Cite
|
Sign up to set email alerts
|

The Polyadenylation Factor Subunit CLEAVAGE AND POLYADENYLATION SPECIFICITY FACTOR30: A Key Factor of Programmed Cell Death and a Regulator of Immunity in Arabidopsis  

Abstract: Programmed cell death (PCD) is essential for several aspects of plant life, including development and stress responses. Indeed, incompatible plant-pathogen interactions are well known to induce the hypersensitive response, a localized cell death. Mutational analyses have identified several key PCD components, and we recently identified the mips1 mutant of Arabidopsis (Arabidopsis thaliana), which is deficient for the key enzyme catalyzing the limiting step of myoinositol synthesis. One of the most striking fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 79 publications
7
59
0
Order By: Relevance
“…It confirms our previous work (Bruggeman et al, 2014), showing that although lesion formation was totally abolished in the mips1 oxt6 double mutant, defects in root elongation were still present and that rescue of the cotyledon phenotype was only partial, suggesting that these two developmental pathways are only partly dependent on the spontaneous cell death phenotype. This observation further supports the notion that HXK-dependent regulation of MIPS2 expression according to growth conditions is a key component of MI-dependent PCD regulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It confirms our previous work (Bruggeman et al, 2014), showing that although lesion formation was totally abolished in the mips1 oxt6 double mutant, defects in root elongation were still present and that rescue of the cotyledon phenotype was only partial, suggesting that these two developmental pathways are only partly dependent on the spontaneous cell death phenotype. This observation further supports the notion that HXK-dependent regulation of MIPS2 expression according to growth conditions is a key component of MI-dependent PCD regulation.…”
Section: Discussionsupporting
confidence: 91%
“…We showed that CPSF30 activity was required for lesion formation in mips1 via SA-dependant signaling (Bruggeman et al, 2014). Furthermore, CPSF30 activity was also necessary for PCD establishment in cat2, lesion-simulating disease1, constitutive expressor of pathogenesis-related genes5 (cpr5), and mitogenactivated protein kinase4 Arabidopsis mutants, indicating that posttranscriptional regulation plays a key role in the control of PCD.…”
Section: Introductionmentioning
confidence: 94%
“…In mips1, we did not detect a significant difference between leaves displaying lesions and healthy leaves. Furthermore, even in LD when lesion formation was severe, we did not observe a sharp increase in ROI accumulation, indicating that ROI production occurs only locally, consistent with previously obtained results with 3,39-diaminobenzidine staining (Bruggeman et al, 2014).…”
Section: Chlorophyll Accumulation Is Required For the Onset Of Pcd Insupporting
confidence: 92%
“…This was the case even in mips1 mips2/+ sesquimutants, in which MI accumulation is further reduced compared with mips1 single mutants. Data reported here do not support a role for oxidative stress in the onset of PCD in mips1, in line with the finding that the cellular redox status is not altered in mips1 under LD conditions (Bruggeman et al, 2014). The latter hypothesis is further confirmed by the observation that EX-dependent 1 O 2 signaling is not involved in triggering cell death in mips1.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation